Sifat Fisik, Organoleptik dan Daya Simpan Telur Itik dengan Penambahan Ekstrak Jahe (Zingiber Officinale) dalam Media Larutan Garam - Nurohmat Hidayat; Aaf Falahudin; Lili Adam Yuliandri (Tropical Livestock Science Journal, 2026)
This research aims to determine the effect of adding ginger extract (Zingiber officinale) to the salt solution medium on the physical, organoleptic properties and shelf life of salted duck eggs. The experiment was carried out with four treatments, namely without ginger extract (P0), and with the addition of 150 g (P1), 300 g (P2), and 450 g (P3) of ginger extract per liter of salt solution (1 liter of water: 500 g of salt). The results showed that the addition of ginger extract had a significant effect on egg pH, with the best treatment being P1 which reached a pH of 8.76 compared to 8.50 in the control, while weight loss ranged from 2.35% to 4.11% and was not significantly different between treatments. Organoleptically, ginger extract has a significant effect on taste, with the highest value at P1, but has no significant effect on egg white color, egg yolk color, egg white texture, egg yolk texture, aroma, oiliness, or overall acceptability. Based on shelf life tests, salted duck eggs with ginger extract can last up to 3 weeks, while salted duck eggs without ginger extract only last 2 weeks. In conclusion, a dose of 150 g of ginger extract per liter of salt solution is the optimal dose, because it is able to improve physical (egg pH) and organoleptic (taste) quality without causing negative effects on other parameters, as well as extending the shelf life of salted duck eggs from 2 to 3 weeks. These results indicate that the use of ginger extract is a natural innovation that promises to improve the quality and durability of salted egg products.